Metode Komunikasi dalam Penyebaran Pesan Damai melalui Konten di Media Sosial Instagram @gusbahaofficial - Hasan Munadi; Ilah Holilah (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
Instagram social media has become an effective platform for spreading positive messages, including messages of peace, to a wider audience. This study aims to analyze the communication methods used in spreading messages of peace through content on Instagram. With a qualitative approach, this study examines various communication strategies, such as the use of attractive visuals, inspiring narratives, and two-way interactions between content creators and audiences. The results of the study show that content that combines elements of visual aesthetics, relevant messages, and emotional engagement of the audience can create a significant impact in spreading the values ​​of peace. In addition, collaboration with influencers and the use of Instagram features such as Stories, Reels, and Live have also proven effective in expanding the reach of messages. This study provides recommendations for communicators, activists, and organizations to optimally utilize Instagram as a medium for spreading messages of peace, while still paying attention to ethics and social responsibility in communicating.